ISAK 335-Based Temple Accounting System Design in Financial Reporting : (Study at Puseh Temple, Banjar Dwi Dharma, Tri Rukun Village, Wonosari District, Boalemo Regency, Gorontalo Province) - Ni Putu Seily Afiani; Lukman Pakaya; Zulkifli Bokiu (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to design a temple accounting system based on ISAK 335 for financial reporting at Puseh Temple, Banjar Dwi Dharma, Tri Rukun Village, Wonosari District, Boalemo Regency, Gorontalo Province, using a descriptive qualitative approach through observation, interviews, and documentation, as well as data validity testing through technical triangulation. The results of the study indicate that financial recording is still simple and limited to cash inflows and outflows, and has not been computerized and is not fully in accordance with ISAK 335. Therefore, this study produces an ISAK 335-based accounting system design using Microsoft Excel (Office 2021) that includes a statement of financial position, a statement of comprehensive income, a statement of changes in net assets, a statement of cash flows, and notes to the financial statements to improve the quality and conformity of temple financial reporting with applicable standards.